Retinopathy among women with hypertensive disorders of pregnancy attending hospitals in Mbarara city, south-western Uganda: a cross-sectional study - Zamaladi, Ibrahimu; Ruvuma, Sam; Mceniery, Carmel M; Kwaga, Teddy; Wilkinson, Ian B; Atwine, Daniel; Lugobe, Henry Mark (BMJ open, 2023)
Objective: Retinopathy is one of the complications occurring among women with hypertensive disorders of pregnancy. We sought to determine the prevalence and factors associated with retinopathy among women with hypertensive disorders of pregnancy in southwestern Uganda. Design: This was a hospital-based cross-sectional study from November 2019 to March 2020. Setting: Three selected hospitals in Mbarara city, south-western Uganda. Participants: The study included all pregnant women with hypertensive disorders of pregnancy. Primary and secondary outcome measures The participants were screened for retinopathy using a fundus camera. Data on participant’s socio-demographics, obstetrics and medical factors were collected. The prevalence of retinopathy was determined and multivariable logistic regression was used to determine the independent factors associated with retinopathy. Results: A total of 216 women with hypertensive disorders of pregnancy were enrolled in this study. The prevalence of retinopathy was 60.2% (130/216). The most common retinal lesions were grade 1 retinopathy (narrowing of arterioles) accounting for 86.9% (113/130), grade 3 (retinal haemorrhages) was present in 10% (13/130) of women and grade 4 (papilloedema) in 3% (4/130). In an adjusted analysis, severe hypertension was significantly associated with retinopathy (aOR=2.8; 95% CI: 1.36 to 5.68). Grandmultigravida women were also associated with retinopathy (aOR=2.4; 95% CI: 0.99 to 5.72) with a tendency towards significancy, p=0.051. Conclusions: In our study, retinopathy was common among women with hypertensive disorders of pregnancy. Women presenting with severe hypertension were likely to have retinopathy. There is a need to integrate screening for retinopathy in the care cascade of women with hypertensive disorders of pregnancy.
Keywords: Retinopathy; Hospitals; Hypertensive disorders; Pregnant women; Uganda